2010
DOI: 10.1007/s00330-010-1884-6
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging goes postmortem: noninvasive detection and assessment of myocardial infarction by postmortem MRI

Abstract: Background Clinical autopsy numbers are decreasing since years and this negative trend

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 36 publications
5
40
0
1
Order By: Relevance
“…They found that acute infarction [survival time: day(s)], subacute infarction [survival time: week(s)], and chronic infarction or scars [survival time: month(s)] can be identified on PMMR. 31,67,68 The post-mortem imaging findings of acute myocardial infarction are comparable to those found in clinical cardiac MR and consist of focal necrosis surrounded by perifocal myocardial oedema with increased signal intensity on T 2 weighted images ( Figure 10). 31,45 In a number of cases where circumstantial evidence was suggestive for sudden cardiac death, Jackowski et al 31,67,68 noted a focally decreased signal intensity within the myocardium on T 2 weighted images without perifocal oedema.…”
Section: Cardiovascular Imagingmentioning
confidence: 56%
See 2 more Smart Citations
“…They found that acute infarction [survival time: day(s)], subacute infarction [survival time: week(s)], and chronic infarction or scars [survival time: month(s)] can be identified on PMMR. 31,67,68 The post-mortem imaging findings of acute myocardial infarction are comparable to those found in clinical cardiac MR and consist of focal necrosis surrounded by perifocal myocardial oedema with increased signal intensity on T 2 weighted images ( Figure 10). 31,45 In a number of cases where circumstantial evidence was suggestive for sudden cardiac death, Jackowski et al 31,67,68 noted a focally decreased signal intensity within the myocardium on T 2 weighted images without perifocal oedema.…”
Section: Cardiovascular Imagingmentioning
confidence: 56%
“…31,67,68 The post-mortem imaging findings of acute myocardial infarction are comparable to those found in clinical cardiac MR and consist of focal necrosis surrounded by perifocal myocardial oedema with increased signal intensity on T 2 weighted images ( Figure 10). 31,45 In a number of cases where circumstantial evidence was suggestive for sudden cardiac death, Jackowski et al 31,67,68 noted a focally decreased signal intensity within the myocardium on T 2 weighted images without perifocal oedema. This finding was interpreted as a sign of early acute myocardial infarction (survival time: minutes to hours), and recently, Jackowski et al 68 published a new study which supports this interpretation.…”
Section: Cardiovascular Imagingmentioning
confidence: 56%
See 1 more Smart Citation
“…Angiography is a promising soft tissue imaging technique, however, more studies are needed to determine its potential. Post-mortem magnetic resonance imaging does not have this limitation and can identify soft tissue lesions [11], but its accessibility is more limited than MDCT or CT-angiography and its usefulness is still being evaluated for post-mortem examinations. Postmortem CT-angiography and cardiac MRI have their advantages and disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies, however, have highlighted its limited application and low accuracy in cases of natural deaths, especially in the field of cardiovascular pathology [10]. At the same time, some pioneer studies involving postmortem MDCTangiography and cardiac pathologies have recently been published [11][12][13] describing the potential to overcome these weaknesses. Several authors suggest that the major limitations concerning cardio-vascular pathology could be minimized by the introduction of postmortem angiography [12,14,15].…”
Section: Introductionmentioning
confidence: 99%